ENGLISH-GRANDEUR OF MERAAJ-E-MUHAMAMD SAAW AND TELEPORTATION: A RELIGIO- SCIENTIFIC EXPLANATORY STUDY - Syed Aftab Alam; Naheed Arain (دی اسکالر, 2018)
Islam conveys the latest and the most practicable rules for leading a perfect life on earth and also depicts the true incidents of life of hereafter. Incidents of life hereafter are told by the Holy Prophet Muhammad SAAW after his travel from earth to Heavens. Millions people were not admitting this travel so ultimately they deny the information about the life of hereafter described by the Holy Prophet. It is evident that the people of oldest era had some spiritual powers or knowledge of the book that they can travel around the globe or towards bright stars without consuming time. The learned scientists of this era has invented such medias of travelling that has defeated unbelievable hurdles of time and space and now they are again reaching at the level of such scientific knowledge that they are saying that a human being can be travelled from earth to the space without spending time. The theories of relativity and Quantum bond, experiments of teleportation and transportation of photons in space are fore saying of human transportation. It is concluded that present knowledge of scientific experiments are near to admit that the travel of Holy Prophet Muhammad SAAW is admit able and logical.